2020
DOI: 10.1002/mgg3.1386
|View full text |Cite
|
Sign up to set email alerts
|

(Epi)genetic profiling of extraembryonic and postnatal tissues from female monozygotic twins discordant for Beckwith–Wiedemann syndrome

Abstract: Background Beckwith–Wiedemann syndrome (BWS) is an overgrowth disorder caused by defects at the 11p15.5 imprinted region. Many cases of female monozygotic (MZ) twins discordant for BWS have been reported, but no definitive conclusions have been drawn regarding the link between epigenetic defects, twinning process, and gender. Here, we report a comprehensive characterization and follow‐up of female MZ twins discordant for BWS. Methods Methylation pattern at 11p15.5 and multilocus methylation disturbance (MLID) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…We recently investigated a MZ female twin pair discordant for BWS by analyzing MLID and the XCI pattern. We found that the affected twin carried IC2 LOM and MLID in both blood and buccal swab, while the healthy twin presented IC2 LOM and MLID only in blood, probably as a consequence of placental vascular connections [ 11 ]. These results suggest a common pathomechanism leading to IC2 LOM and MLID that acts either after the twinning event and/or forces the segregation of the epimutated cells to one embryo.…”
Section: Deciphering the Timing Of Epigenetic Errors Establishmentmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently investigated a MZ female twin pair discordant for BWS by analyzing MLID and the XCI pattern. We found that the affected twin carried IC2 LOM and MLID in both blood and buccal swab, while the healthy twin presented IC2 LOM and MLID only in blood, probably as a consequence of placental vascular connections [ 11 ]. These results suggest a common pathomechanism leading to IC2 LOM and MLID that acts either after the twinning event and/or forces the segregation of the epimutated cells to one embryo.…”
Section: Deciphering the Timing Of Epigenetic Errors Establishmentmentioning
confidence: 99%
“…These results suggest a common pathomechanism leading to IC2 LOM and MLID that acts either after the twinning event and/or forces the segregation of the epimutated cells to one embryo. Regarding the XCI pattern, since both twins presented the same skewed XCI, we hypothesized that the establishment of XCI precedes and may trigger IC2 LOM and MLID [ 11 ]. Interestingly, deviations from the random pattern of XCI has been already reported in non-X-linked diseases [ 98 ].…”
Section: Deciphering the Timing Of Epigenetic Errors Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of diffused mosaicism was suggested by Cohen et al [29] and has been accepted by others [38,39]. Complementary to this theory, we recently proposed the theory of epigenetic burden to suggest potential phenotypic consequence of diffused epigenetic mosaicism in the context of IC2 LOM and BWSp [26].…”
Section: Discussionmentioning
confidence: 67%
“…Diffused epigenetic mosaicism has been proposed to describe the phenotypic divergence that can occur between twins affected by BWSp ( Cohen et al 2019 ). More recently, case reports have provided support for this theory ( Fontana et al 2020 ; Sun et al 2021 ); however, no direct evidence demonstrating the tissue mosaicism exists to date.…”
Section: Introductionmentioning
confidence: 99%